Implementation of non-positional digital filters - Veligosha, A. V.; Linets, G. I.; Kaplun, D. I.; Klionskiy, D. M.; Bogaevskiy, D. V. (2016 XIX IEEE International Conference on Soft Computing and Measurements (SCM), 2016)
We consider the implementation of non-positional digital filters of parallel-pipeline type with the required accuracy, computational speed, and frequency response. The approaches suggested in the paper can be used for designing high-rate digital filters.